Language methodology, learners’ strategies and motivation as determining factors in the learners’ success in french language (2011)
Affirming that French Language is unavoidably important and indispensable in Nigeria is not an overstatement. Nigeria is a giant of Africa and in view of the roles she plays in the international politics in Africa, she needs French language more than any other essential resources one may think of. . This assertion is quiet sound because of the great number of Francophone countries that surround Nigeria and the diplomatic and economic ties between Nigeria and the neighbouring French speaking countries. The decline in the study of French language in Nigeria has been a major concern to the stakeholders in the field of French language education. Many researchers in this field have made frantic efforts to unravel the misery behind the slow pace of development in the study of French in Nigeria. Ogike (2005) opines that the problem that has bedeviled the teaching of French language after the political independence is beyond the control of the Nigerian French teachers. These factors responsible for this decline are multifaceted. This paper discusses the concept of language teaching methodology as an excruciating phenomenon in the success in language learning. Methodology of language learning cannot be under estimated while discussing the issue of foreign language education. In addition, the paper discusses the learners learning strategies in foreign language learning situation. Finally, the concept of motivation towards language learning would be considered in the light of the teachers' motivational skills.